Gregory Bateson’s Ecology of Mind and the Understanding of Human Knowledge - Elzbieta Magdalena Wasik (Romanian Journal of Communications and Public Relations, 2017)
Departing from the biological notion of ecology that pertains to mutual relationships between organisms and their environments, this paper discusses theoretical foundations of research on the nature of human mind in relation to knowledge, cognition and communication conducted in a broader context of social sciences. It exposes the view, explicitly formulated by Gregory Bateson, that the mind is the way in which ideas are created, or just the systemic device for transmitting information in the world of all living species. In consequence, some crucial points of Bateson’s reasoning are accentuated, such as the recognition of the biological unity of organism and environment, the conviction of the necessity to study the ecology in terms of the economics of energy and material and/or the economy of information, the belief that consciousness distorts information coming to the organism from the inside and outside, which is the cause of its functional disadaptation, and the like. The conception of the ecology of an overall mind, as the sets of ideas, notions or thoughts in the whole world, is presented against the background of theoretical and empirical achievements of botany and zoology, anthropology, ethology and psychiatry, sociology and communication studies in connection with the development of cybernetics, systems theory and information theory.